THE IMPORTANCE OF INTERNATIONAL COOPERATION IN THE FIGHT AGAINST HUMAN TRAFFICKING - Urakov Dzhahongir Rajabovich (Scholar Express Journals, 2023)
The article states that human trafficking poses a serious threat to human civilization, the development of society and the development of states. Therefore, the fight against organized crime, in particular, international terrorism, drug business, illegal sale of arms, and any form of human trafficking, is an urgent problem for the public today.
Keywords: human trafficking; legislation to combat human trafficking; mass migration; traffic